Compact cities and economic productivity in Mexico. (August 2020) - Monkkonen, Paavo; Montejano, Jorge; Guerra, Erick; Caudillo, Camilo
This paper examines the contingent nature of agglomeration economies. Existing empirical evidence that compact cities are more productive is mostly from countries and regions with highly productive service sectors, such as the USA or Europe. We hypothesise that this relationship will differ in countries where land-intensive manufacturing activities are more productive than services. In this paper, we test this hypothesis using data from the 100 largest cities in Mexico in 1990, 2000 and 2010. Under a number of specifications, we find that the most common measures of urban compactness are, in fact, negatively associated with economic productivity. This holds even when instrumenting urban spatial structure with the underlying geology of urban areas. The findings suggest a need for greater attention to national economic structure in the study of agglomeration economies, and that policy agendas focused on compact urbanisation take account of the needs of the manufacturing sector.